Abu Nasr Farabi’s Pedagogical Views on Education and Upbringing (International Journal of Scientific Trends, 2026)
This article analyzes the pedagogical views of the great Eastern thinker Abu Nasr Farabi on the process of education and upbringing from philosophical and pedagogical perspectives. The study highlights the thinker’s ideas about human perfection, the role of knowledge in the development of society, moral education, and the teacher–student relationship. Furthermore, Farabi’s didactic principles aimed at forming a well-rounded and morally mature individual are examined, as well as their significance for the modern education system.